Motivational Drivers of Heavy Work Investment: Intercultural Comparison between USA and Middle East - Garas, Lydia (East Carolina University, 2022)
In the current study, we examined the motivational correlates of both types of Heavy Work Investment (HWI) based on the self-determination theory of motivation, while controlling for job demands and resources. Consequently, the results of this analysis were compared among two different cultures (i.e., USA and Middle East). Furthermore, based on the results, a series of moderation analyses was conducted to explore potential moderation effects of four cultural dimensions (i.e., individualism, power distance, uncertainty avoidance, and masculinity). Overall, more focus has been given to outcomes of HWI types rather than their underlying motives. Moreover, the scarcity of random cross-cultural samples is a gap in the extant research, challenging the generalization of the current literature. The final sample included 632 full-time employees at a large Southeastern university in the U.S., a snowball sample in Egypt, and full-time employees at a large university in the UAE. The results showed workaholism is positively associated with the non-self-determined types of motivation (i.e., extrinsic and introjected regulation), while work engagement is positively related to the self-determined types of motivation (i.e., intrinsic and identified regulation), and negatively associated with extrinsic motivation. Furthermore, cultural masculinity moderated the motivational correlates of work engagement, as well as the relationship between workaholism and introjected regulation. Future research, organizational implications, and study limitations are addressed.
Keywords: Work Engagement; Culture; Job enrichment--Southern States; Job enrichment--Egypt; Job enrichment--United Arab Emirates; Workaholism--Southern States; Workaholism--Egypt; Workaholism--United Arab Emirates; Employee motivation--Southern States; Employee motivation--Egypt; Employee motivation--United Arab Emirates